Use of Pro-Long to extend the storage life of avocados - Hussein H.T. Tarimo (1982)
The effect of Pro-Long on the storage life of avocados (Persea americana Mill.) varieties Fuerte and Hass was investigated. 1.5% to 1.8% Pro-Long for Fuerte variety were found to be the optimum concentrations to reduce weight loss, retard respiratory rate and ripening. Other changes assessed during storage include chlorophyll, carotenoid, ascorbic acid, moisture, lipid, sugar and phenolic content, texture, acidity and organoleptic properties. Pro-Long also imparted a gloss to the fruit which is an added advantage. [Continues.]